Broad antiviral and anti‐inflammatory efficacy of nafamostat against SARS‐CoV‐2 and seasonal coronaviruses in primary human bronchiolar epithelia. Issue 2 (30th June 2021) - Niemeyer, Brian F.; Miller, Caitlin M.; Ledesma‐Feliciano, Carmen; Morrison, James H.; Jimenez‐Valdes, Rocio; Clifton, Clarissa; Poeschla, Eric M.; Benam, Kambez H.
Abstract: Antiviral strategies that target host systems needed for SARS‐CoV‐2 replication and pathogenesis may have therapeutic potential and help mitigate resistance development. Here, we evaluate nafamostat mesylate, a potent broad‐spectrum serine protease inhibitor that blocks host protease activation of the viral spike protein. SARS‐CoV‐2 is used to infect human polarized mucociliated primary bronchiolar epithelia reconstituted with cells derived from healthy donors, smokers and subjects with chronic obstructive pulmonary disease. Nafamostat markedly inhibits apical shedding of SARS‐CoV‐2 from all donors (log10 reduction). We also observe, for the first‐time, anti‐inflammatory effects of nafamostat on airway epithelia independent of its antiviral effects, suggesting a dual therapeutic advantage in the treatment of COVID‐19. Nafamostat also exhibits antiviral properties against the seasonal human coronaviruses 229E and NL6. These findings suggest therapeutic promise for nafamostat in treating SARS‐CoV‐2 and other human coronaviruses. Abstract : Nafamostat mesylate exhibits direct antiviral activity against novel SARS‐CoV‐2 and seasonal coronaviruses in infected primary human airway epithelium. These antiviral properties appear to be mediated, in part, through host serine protease TMPRSS2. Additionally, nafamostat reduces production of pro‐inflammatory cytokines from epithelial cells independent of virus infection, showing strong therapeutic potential for respiratory infections associated with high levels of inflammation.